Age‐Specific Impact of Self‐Monitored Pulse Pressure on Hypertensive Target Organ Damage in Treated Hypertensive Patients - Eguchi, Kazuo (J Clin Hypertens (Greenwich), 2007)
The authors examined the relationship of clinic and self‐measured pulse pressure with target organ damage in 597 treated hypertensive patients without clinical evidence of renal dysfunction or a history of heart failure. The cross‐sectional relationships of plasma brain natriuretic peptide (BNP) and urinary albumin/creatinine ratio with clinic and self‐monitored pulse pressures were estimated in age tertile groups: younger than 67 years (n=193), 67 to 75 years (n=216), and older than 75 years (n=188), controlling for various confounding factors. In multivariable analyses, both clinic and self‐monitored higher pulse pressures were associated with increased urinary albumin/creatinine ratio in all 3 age groups. Self‐monitored higher pulse pressure, but not clinic pulse pressure, was consistently associated with increased BNP in the younger and middle‐aged patients. In the very old (older than 75 years), however, there were no consistent associations between pulse pressure measures and BNP. More studies are needed in the evaluation of cardiac risk with hemodynamic measures in the very old.